The anti-aesthetic: Essays on postmodern culture - Foster, Donald H. (New York The new Press, 1998)
A continuing best-seller -- with more than 60,000 copies sold -- The Anti-Aesthetic is a touchstone volume for postmodern debate and theory. Though the cultural stakes and terms have changed over the last decade, this collection still illuminates -- perhaps now even more lucidly -- a vital current in contemporary criticism.